Correlates of Objectively Measured Sitting Time in South Korean Adults: 2014–2015 Korea National Health and Nutrition Examination Survey - Lee, Hyo; Lee, Miyoung (Frontiers in Public Health, 2022)
The purpose of this study was to investigate daily amounts of time spent sitting and frequency of breaks from sitting and to identify their sociodemographic, environmental, and health behavioral correlates for Korean adults (age = 19-65). This study analyzed accelerometer subdata from the 2014–2015 Korea National Health and Nutrition Examination Survey (n=1,768). Ordinary least squares regression models stratified by weekday and weekend were tested to identify correlates of time spent sitting and number of sitting breaks. The average daily amounts of sitting time during weekdays and weekends were 500.63 minutes (95% confidence interval [CI] = 495.20–506.06) and 488.10 minutes (95% CI = 481.72–494.49), respectively. On weekdays and weekends, the average numbers of breaks from sitting per hour were 6.62 (95% CI = 6.57–6.68) and 6.60 (95% CI = 6.54–6.66), respectively. The participants with the greatest daily sitting time tended to be male, middle-aged, never married, office workers, and residents of a metropolis; tended to have a high school educational level or higher; and had never smoked, were underweight, were physically inactive, and slept less than 6 hours a day. Fewer breaks from sitting was associated with being male, never married, middle-aged, an office worker, an apartment resident, never having smoked, and underweight. Higher education level and physical inactivity were associated with more frequent breaks from sitting. To reduce sedentary behavior, this study helps identify at-risk populations and their characteristics. Future studies should incorporate longitudinal data and measure domain-specific sedentary behavior.